New Media Resources for Indigenous Researcher Training : Fellowship Report. - O’Sullivan, Sandy (Australian Learning and Teaching Council (ALTC), 2011)
Report from a fellowship that stimulated Indigenous research students and their supervisors to consider how new media forms of dissemination, such as image/sound, film, exhibition and digital media, may form culturally appropriate alternatives or adjuncts to the linear, written thesis form.